The heritage values of Arab District, Erbil City, Iraq - Akram, Omar Khasro; Ismail, Sumarni; Franco, Daniel Jose (International Journal of Engineering Technology, Management and Applied Science, 2016)
The Arab District is located in the Erbil City, near to the well-known Erbil Citadel, and its considered one of the most important districts of Erbil. Although its importance, it is not easy to find good information sources about the growth of this district, being most of the information known by visitor’s pictures, which were painted or taken while visiting the place, or by interviewing the local people. This paper addresses this district, focusing essentially on the population and their houses, identifying not just the community, which was formed by Muslims and Christians, but also the houses topology and types. Using the statistical study (“census”) of Arab District, it is also possible to understand how the population increased and decreased through the years, being 1975 in the year of 2015. Besides the population analysis, it is also enumerated some of the district characteristics, like weakness and opportunities, ending with a descriptive and interpretative approach in a way to outline the government decisions.